2021
DOI: 10.1002/bem.22360
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Hypomagnetic Field: Ground‐Based Data for Space Exploration

Abstract: The future of mankind is tied to the exploration and eventual colonization of space. Currently, people have resided in orbit at a space station. In the future, we will have opportunities to stay on the moon, Mars, or in deeper space, where astronauts are exposed to the hypomagnetic field (HMF), which refers to an extremely weak magnetic field environment compared with the geomagnetic field. However, the potential risks of HMF exposure to human health are often overlooked. Here, we summarize the literature rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 89 publications
0
17
0
Order By: Relevance
“…Beyond these, there is little research on other systems. HMF can affect the function of multiple systems in an organism, especially in the central nervous system ( Zhang et al, 2021b ). Similarly, microgravity can affect the central nervous system while the combined effects of HMF and microgravity is yet to be elucidated.…”
Section: Combined Biological Effects Of Space Environmental Factors I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond these, there is little research on other systems. HMF can affect the function of multiple systems in an organism, especially in the central nervous system ( Zhang et al, 2021b ). Similarly, microgravity can affect the central nervous system while the combined effects of HMF and microgravity is yet to be elucidated.…”
Section: Combined Biological Effects Of Space Environmental Factors I...mentioning
confidence: 99%
“…Astronauts are inevitably exposed to HMF conditions when performing long-cycle and long-distance space missions. HMF can interfere with a variety of functions of organisms, including gene expression, individual growth, embryonic development, learning and working abilities ( Zhang et al, 2021a ; Zhang et al, 2021b ). The orbit of a spacecraft in low orbit around the earth is about 90 min ( Dijk et al, 2001 ; Thirsk et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that the elimination of the geoMF causes a variety of biological responses; see, e.g., recent experimental studies [ 77 , 78 , 79 , 80 , 81 ] and reviews [ 22 , 82 ]. In [ 40 , 83 ], it has been shown that significant changes in the dynamics of moments occur in the “zero,” or hypomagnetic, MF, when the gap between the Zeeman sublevels becomes comparable to the width of the levels themselves.…”
Section: Can the Sensitivity Of Organisms To Tens Of Nt Be Explained?mentioning
confidence: 99%
“…Earth's geomagnetic field, ranging from ∼24 to ∼66 µT depending on latitude 144 , can have critical roles in numerous biological processes. Shielding the geomagnetic field, called hypomagnetic field, is known to cause biological effects 19,22,24,[145][146][147][148][149] .…”
Section: Hypomagnetic Fieldmentioning
confidence: 99%